2009
DOI: 10.1007/s11120-009-9470-y
|View full text |Cite
|
Sign up to set email alerts
|

Selection of plastid- and nuclear-encoded reference genes to study the effect of altered endogenous cytokinin content on photosynthesis genes in Nicotiana tabacum

Abstract: Selection and use of appropriate reference genes as internal controls in real-time reverse transcription PCR (RT-PCR) assays is highly important for accurate quantification of gene expression levels. Since some photosynthetic genes are encoded in the nuclear genome and others in the chloroplast genome, we evaluated both nuclear-and plastid-encoded candidate reference genes. Six plastid-encoded candidate reference genes were derived from Arabidopsis microarray data and three plastid-and five nuclear-encoded ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
(44 reference statements)
1
21
0
Order By: Relevance
“…2; Table 2) were ranked poorly based on the two softwares in this study, indicating that these genes should be avoided as internal controls when analyzing gene expression levels in A. mongolicus under abiotic stresses, whereas tubulin (Cortleven et al 2009;de Almeida et al 2010), ATPbinding cassettes transporter gene (Libauh et al 2008) and elongation factor gene (Nicot et al 2005;Tong et al 2009), have been reported to be invariant genes in other studies. Fig.…”
Section: Discussionmentioning
confidence: 77%
“…2; Table 2) were ranked poorly based on the two softwares in this study, indicating that these genes should be avoided as internal controls when analyzing gene expression levels in A. mongolicus under abiotic stresses, whereas tubulin (Cortleven et al 2009;de Almeida et al 2010), ATPbinding cassettes transporter gene (Libauh et al 2008) and elongation factor gene (Nicot et al 2005;Tong et al 2009), have been reported to be invariant genes in other studies. Fig.…”
Section: Discussionmentioning
confidence: 77%
“…This is unsurprising since both genes demonstrate significant variation in many different organisms and experimental contexts (Dheda et al 2004;Nicot et al 2005;Jain et al 2006;Reid et al 2006). In contrast, Cortleven et al (2009) identified atubulin as one of the most stable reference genes in tobacco. However, this conclusion was based on a combined analysis of wildtype and transgenic plants, and may be specific to the lines tested.…”
Section: Discussionmentioning
confidence: 88%
“…These characteristics have encouraged the widespread use of N. tabacum in studies of plant stress responses (Kanneganti and Gupta 2008), gene expression (Delaney et al 2007), protein transport and localization (Delaney et al 2007), industrial protein production (Bock 2007), organ development (Volkov et al 2005;Ribarits et al 2007) and plastid evolution (Sheppard et al 2008). RT-PCR is commonly used to analyze gene expression in tobacco, and eight nuclear-encoded 'housekeeping' genes have been used as internal references in RT-PCR and Northern analysis of tobacco gene expression (Dean et al 2002;Volkov et al 2005;Kasukabe et al 2006;Ribarits et al 2007;Cortleven et al 2009). However, the relative stability of these and other potential reference genes in tobacco has not been studied in a range of experimental contexts, and this has constrained the use of real-time PCR in the tobacco system.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown the varied transcript level of the housekeeping genes under different environmental conditions (Jian et al, 2008;Maroufi et al, 2010). Several studies showed differential stabilities of different internal control genes which can be used for transcript level studies under any experimental condition (Exposito-Rodriguez et al, 2008;Cortleven et al, 2009;Artico et al, 2010). For more clarity, two or more reference genes can also be used for perfect interpretation of quantitative PCR data.…”
Section: Discussionmentioning
confidence: 99%